2019
DOI: 10.1111/1346-8138.14847
|View full text |Cite
|
Sign up to set email alerts
|

Location of infantile hemangioma is a predictor of volumetric sequelae after involution

Abstract: Although infantile hemangiomas (IH) spontaneously involute, some leave more volumetric sequelae than others. Identifying predictors of such sequelae would provide a management reference for IH lesions and help achieve favorable outcomes. Our objective is to explore the correlation between volumetric residue remaining after IH involution and its location and to identify other potential outcome predictors. All IH patients examined at our hospital from 2008 to 2011 were reviewed, and both the degree of volumetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Previous studies reported that more than half of untreated IH left residual lesions after regression; and the most common sequelae were telangiectasia, fibrofatty residue and scars 2,3 . Moreover, IH in the central facial region, including the eyelids, nose and lips, had a higher risk of permanent sequelae after regression 17 …”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported that more than half of untreated IH left residual lesions after regression; and the most common sequelae were telangiectasia, fibrofatty residue and scars 2,3 . Moreover, IH in the central facial region, including the eyelids, nose and lips, had a higher risk of permanent sequelae after regression 17 …”
Section: Discussionmentioning
confidence: 98%
“…After 8 months of treatment, the lesion thickness was 1.5 mm (regression rate = 21.1%). In the vast majority of researchs on IHs, the regression rate was traditionally defined by subjective outcome evaluations, such as a VAS 19,20 or GAS, 10 based on the improvement of the most important characteristics of IHs (thickness and/or color of superficial IHs, 10,19,20 and volume of deep or mixed IHs 7,21 ). To improve accuracy and credibility, Bingham 22 Although color is also an important characteristic of IH, the therapeutic regimen for IH is largely not determined based on color.…”
Section: Resultsmentioning
confidence: 99%
“…To assess whether the overall effect of oral propranolol treatment for IHs could commensurate that of spontaneous involution, we designed a matched comparative study to eliminate 2 known confounding factors [1][2][3] and investigate the long-term outcome of these propranololtreated and untreated lesions. To avoid selection bias while maintaining comparability, the cases were paired according to their original documented pictures, without knowing their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…We selected from patient cohorts of those who received oral propranolol therapy for their IH and those who adopted the wait-and-see method. Patients from the oral propranolol cohort were individually matched with a patient from the untreated cohort, whose lesion has a similar location and morphology, which have both been considered risk factors for leaving sequelae 1,2 . The remaining patients of the oral propranolol therapy cohort whom we were unable to pair with an untreated patient were omitted from this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation